Pilot Study on Quality of Life and Sexual Function in Men‐Who‐Have‐Sex‐with‐Men Treated for Prostate Cancer. (6th June 2013) - Lee, Tsz Kin; Breau, Rodney Henry; Eapen, Libni
Abstract: Introduction: There is limited data on post‐treatment quality of life (QoL) for men‐who‐have‐sex‐with‐men (MSM) with prostate cancer (PCa). QoL in MSM may not be reflected by assessment tools designed for the heterosexual population. Aims: Our goals were to evaluate post‐treatment QoL in PCa patients who are MSM, and to investigate the utility of current QoL assessment tool. Methods: PCa patients treated with surgery and/or radiation were recruited from the local MSM community. Each participant completed the Expanded Prostate Cancer Index Composite (EPIC) questionnaire, Male Sexual Health Questionnaire (MSHQ), and a questionnaire focused on insertive and receptive roles of anal intercourse. Main Outcome Measures: Response scores were calculated based on questionnaire design and compared by treatment modality. Results: Seven participants treated with surgery (mean age 58) and eight participants treated with radiation (mean age 67) were recruited. No participant in the surgical group received androgen deprivation therapy (ADT) while two in radiation group were treated with ADT. The sample size of this study did not permit formal statistical analysis, although potential differences in Urinary and Bowel Domains from EPIC and Ejaculation Scale from MSHQ were observed. More participants from the radiation group seemed to be able to maintain both insertive and receptive anal intercourse roles after treatment compared to participants who received surgery. Conclusions: While the two validated assessment tools suggested similar QoL scores including sexual function for both surgical and radiation groups, post‐treatment sexual function related to anal intercourse may be better in the radiation group, as compared to the surgical group. Larger studies in PCa patients from MSM community are warranted to verify these data.Lee TK, Breau RH, and Eapen L. Pilot study on quality of life and sexual function in men‐who‐have‐sex‐with‐men treated for prostate cancer. J Sex Med 2013;10:2094–2100.